2022
DOI: 10.1002/ar.24863
|View full text |Cite
|
Sign up to set email alerts
|

A global perspective on embryological and fetal collections: Where to from here?

Abstract: Human fetal and embryos collections (FECs) peaked in the late 19th century, an era before informed consent, and hence have unclear provenance. These collections are not only historical artifacts, but prized resources for education and research. This study aimed to determine, via a narrative review, the present location, status, and profile of reported human fetal and embryonic collections. Twenty-seven articles that reported on collections appropriate to the study were selected from an initial search pool of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 60 publications
0
14
0
Order By: Relevance
“…Regarding the present study, narrative review was the preferred method as this approach was deemed as ideal to address the diverse aspects of the topic in terms of core concepts, published data, scientific resources and existing knowledge gaps [22]. Moreover, narrative review was found to be suitable in view of the fact that diverse methodologies were followed and taking into consideration the essentially descriptive nature of selected studies [18]. The literature search undertaken for this study was based on inclusion and exclusion criteria that were set after deciding the topic but before conducting literature search (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…Regarding the present study, narrative review was the preferred method as this approach was deemed as ideal to address the diverse aspects of the topic in terms of core concepts, published data, scientific resources and existing knowledge gaps [22]. Moreover, narrative review was found to be suitable in view of the fact that diverse methodologies were followed and taking into consideration the essentially descriptive nature of selected studies [18]. The literature search undertaken for this study was based on inclusion and exclusion criteria that were set after deciding the topic but before conducting literature search (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…For the present study, narrative review was the selected method as it was deemed that realistically this approach is ideal to address the topic in terms main concepts, theories, sources, and knowledge gaps (Gregory & Denniss, 2018 ). Moreover, narrative review was found to be suitable in view of divergent methodologies followed and essentially descriptive nature of selected studies (El‐Haddad et al, 2022 ). The literature search undertaken for this study was based on inclusion and exclusion criteria that were set after deciding the topic but before conducting literature search (Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…11 Historically, most fetal and embryological remains for collections were obtained from obstetricians and gynecologists without obtaining informed consent from the next of kin. 1,26 Today, in Australia it is unclear whether obstetricians can still donate fetal remains to anatomical institutions. The guidelines as set out by National Health and Medical Research Council and Research Involving Human Embryos Act 27 are still also unclear of who consent should be obtained from for research purposes regarding fetal and embryo tissue, cells, and genetics (to biobanks rather than anatomical collections).…”
Section: Challenges Of Informed Consentmentioning
confidence: 99%
“…Not only will the integration foster an inclusive people-focused learning environment but will also embed professionalism and amplify the evolving views on the concept of informed consent. 1 The resulting transparent discourse will aid in building trust between institutions that curate human fetal and embryological collections and/or hold human embryo and fetal tissue and the wider community. This provides opportunities to co-design important frameworks, such as that of informed consent, with the community.…”
Section: Introductionmentioning
confidence: 99%